Dinamika Problem-Focused Coping Menuju Resiliensi Akademik: Studi Fenomenologis Pada Mahasiswa Tingkat Akhir - Siti Paijatun Solehah; Cut Mellyza Rizka (IDEA: Jurnal Psikologi, 2026)
This study aims to explore in depth the dynamics of Problem-Focused Coping (PFC) in building academic resilience among final-year Psychology students currently composing their undergraduate theses. Final-year students often encounter intense academic pressures manifested in anxiety, research stagnation, and interpersonal conflicts with supervisors. Employing a qualitative approach with an interpretative phenomenological design, this research uncovers the essence of participants' conscious experiences in managing these pressures. Data were collected through in-depth interviews with three informants selected via purposive sampling and analyzed using Interpretative Phenomenological Analysis (IPA). The results indicate that PFC dynamics represent a transformative process extending beyond technical task completion, creating a mechanism termed "agency ritualism." Active coping strategies such as structured scheduling, the courage to engage in intellectual confrontation, and reference navigation function as "psychological anchors" that restore self-esteem and a sense of self-control from a state of learned helplessness. Psychology students possess a unique "double reflection" capability, wherein they apply mental health theoretical literacy to perform independent cognitive restructuring. The psychological transition moves from an agency crisis phase to coping initiation, eventually reaching resilience integration, where academic obstacles are redefined as catalysts for a growth mindset. This study concludes that success in building academic resilience heavily depends on a student's ability to interpret every small act of problem-solving as a form of self-sovereignty, which ultimately fosters the mental toughness required to face post-campus challenges. Keywords: Problem-Focused Coping, Academic Resilience, Phenomenology, Psychology Students, Agency Ritualism